2021
DOI: 10.1186/s12951-021-00956-8
|View full text |Cite
|
Sign up to set email alerts
|

Sustained zinc release in cooperation with CaP scaffold promoted bone regeneration via directing stem cell fate and triggering a pro-healing immune stimuli

Abstract: Metal ions have been identified as important bone metabolism regulators and widely used in the field of bone tissue engineering, however their exact role during bone regeneration remains unclear. Herein, the aim of study was to comprehensively explore the interactions between osteoinductive and osteo-immunomodulatory properties of these metal ions. In particular, the osteoinductive role of zinc ions (Zn2+), as well as its interactions with local immune microenvironment during bone healing process, was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 94 publications
(80 reference statements)
2
40
0
Order By: Relevance
“…Low and high concentrations can cause many diseases. Zinc deficiency can inhibit the growth of children as it is involved in bone metabolism [ 7 , 9 ]. It has an effect on the immune system and inhibits inflammation, and its deficiency has been found in children with pneumonia and bronchitis [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low and high concentrations can cause many diseases. Zinc deficiency can inhibit the growth of children as it is involved in bone metabolism [ 7 , 9 ]. It has an effect on the immune system and inhibits inflammation, and its deficiency has been found in children with pneumonia and bronchitis [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway plays a key role during the process of osteogenic and adipogenic differentiation of BMSCs [ 163 ]. As a lipid kinase located in the cytoplasm, PI3K is activated through the stimulation of upstream growth factors, and then PI3K transduces upstream signals from receptors to generate PIP3 [ 164 ].…”
Section: Mechanism Of Msc-evs In Repairing Bone Defectsmentioning
confidence: 99%
“…Huang et al demonstrated that Zn 2+ could promote the polarization of macrophages from M1 to M2 through PI3K/Akt/mTOR pathway. The M2 phenotype polarization of macrophages and the subsequent biological events will create a favorable osteogenic microenvironment ( Huang et al, 2021 ). The immunomodulatory action of Mg 2+ is related to its concentration.…”
Section: Antibacterial Mechanism Of Mg- Zn- and Fe-based Alloys As Or...mentioning
confidence: 99%